Too few women at the top : the persistence of inequality in Japan - Nemoto, Kumiko, 1970- (Ithaca : ILR Press, an imprint of Cornell University Press, 2016)
The number of women in positions of power and authority in Japanese companies has remained small despite the increase in the number of educated women and the passage of legislation on gender equality. In Too Few Women at the Top, Kumiko Nemoto draws on theoretical insights regarding Japan's coordinated capitalism and institutional stasis to challenge claims that the surge in women's education and employment will logically lead to the decline of gender inequality and eventually improve women's status in the Japanese workplace. Nemoto's interviews with diverse groups of workers at three Japanese financial companies and two cosmetics companies in Tokyo reveal the persistence of vertical sex segregation as a cost-saving measure by Japanese companies. Women's advancement is impeded by customs including seniority pay and promotion, track-based hiring of women, long working hours, and the absence of women leaders. Nemoto contends that an improvement in gender equality in the corporate system will require that Japan fundamentally depart from its postwar methods of business management. Only when the static labor market is revitalized through adoption of new systems of cost savings, employee hiring, and rewards will Japanese women advance in their chosen professions. Comparison with the situation in the United States makes the author's analysis of the Japanese case relevant for understanding the dynamics of the glass ceiling in U.S. workplaces as well.
The latent function of sex segregation in the Japanese business system -- The Japanese way of change : recasting institutional coordination, sustaining gender inequality -- Studying sex segregation in five Japanese companies -- Women as cheap labor : salaries, promotions, ghettos, and the culture of woman blaming -- Production and navigation of gender bias : heroic masculinity, female misogyny, and queen bees -- Thwarted ambitions and sympathy : long working hours, sex segregation, and the price of masculinity -- Hostess culture and women's jobs : obligatory femininity and sexual harassment.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
In English.
JSTOR
Keywords: Sex discrimination in employment -- Japan; Sex role in the work environment -- Japan; Sex discrimination against women -- Japan; Women -- Employment -- Japan; Discrimination sexuelle dans l'emploi -- Japon; Rôle selon le sexe en milieu de travail -- Japon; Discrimination à l'égard des femmes -- Japon; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Sex discrimination against women; Sex discrimination in employment; Sex role in the work environment; Women -- Employment; Japan